1995
DOI: 10.1111/1523-1747.ep12612836
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Epidemiology of Pemphigus in Tunisia and France: Unusual Incidence of Pemphigus Foliaceus in Young Tunisian Women

Abstract: Recent studies have suggested that in Tunisia, pemphigus foliaceus is more frequent in young women than expected. To confirm these findings, we compared the incidence rates of pemphigus in Tunisia as a whole and in a large area of France. New cases of pemphigus were detected retrospectively from dermatology departments and pathology laboratories over a 6-year period and classified as pemphigus vulgaris or foliaceus according to the pathology. In France, the incidence rate was 1.7 cases per million per year (95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
193
3
23

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(261 citation statements)
references
References 11 publications
42
193
3
23
Order By: Relevance
“…The sporadic form occurs in western Europe and North America with a low incidence (Ͻ1 case per million per year) and equally affects males and females over 50 years old. 2 The endemic form is observed in different geographic regions particularly in Brazil and Tunisia, and has different epidemiological characteristics. 3 In Brazil, PF is known as folgo selvagem (FS), has a high incidence (25 cases per million per year) and predominantly affects young adults with no sex predominance.…”
Section: Desmoglein 1 Is the Target Antigen And Probably The Initiatimentioning
confidence: 99%
See 1 more Smart Citation
“…The sporadic form occurs in western Europe and North America with a low incidence (Ͻ1 case per million per year) and equally affects males and females over 50 years old. 2 The endemic form is observed in different geographic regions particularly in Brazil and Tunisia, and has different epidemiological characteristics. 3 In Brazil, PF is known as folgo selvagem (FS), has a high incidence (25 cases per million per year) and predominantly affects young adults with no sex predominance.…”
Section: Desmoglein 1 Is the Target Antigen And Probably The Initiatimentioning
confidence: 99%
“…In Tunisia, PF is mainly observed in females р35 years old, among which the incidence rate reaches 15 cases per million per year. 2,3 Patients with sporadic or endemic PF synthesize autoantibodies with similar immunochemical properties and frequently bear the same HLA class II alleles (DRB1*0102 and DRB1*0404), 4,5 The results of our recent case-control study performed on French Caucasian patients and healthy controls showed that the desmoglein 1 gene (DSG1) is polymorphic and that one of its variants is associated with sporadic PF. 6 This observation prompted us to determine whether the endemic form of PF seen in Tunisia is also associated with this polymorphic variant of DSG1.…”
mentioning
confidence: 99%
“…O PFE, também conhecido como pênfigo foliáceo brasileiro e pênfigo foliáceo sul-americano, tem sido descrito em vários outros países das Américas -do México ao norte da Argentina, principalmente Paraguai, Bolívia, Peru, Colômbia, Venezuela -e, recentemente, na Tunísia 8,9 . Neste tipo de pênfigo, os pacientes relatam uma sensação de "queimação" no corpo.…”
Section: Introductionunclassified
“…1 In Europe and the United States, the disease has a low incidence rate (under two cases per million per year) and is predominantly represented by PV. 2 In certain geographical areas of Brazil, PF has a much higher incidence rate (25 cases per million per year) and is called endemic pemphigus or Fogo Selvagem. 3 Recently, pemphigus has also been shown to be more frequent in Tunisia (seven cases per million per year) as a consequence of a higher incidence rate of PF which particularly involves young females.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recently, pemphigus has also been shown to be more frequent in Tunisia (seven cases per million per year) as a consequence of a higher incidence rate of PF which particularly involves young females. 2,4,5 Susceptibility to pemphigus is partly determined by genetic factors among which HLA class II genes have been identified. Indeed, DR4 and DR14 haplotypes and, more precisely, DRB1*0402, DRB1*1401 and DRB1*1404 are strongly associated with PV in different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%